A Large Tuberculous Abscess Mimicking a Retroperitoneal Cystic Mass: A Case Report - Kwang Suk Kim; Seunghwan Cha; Jihyun Ahn; Miyeon Cho (대한영상의학회지, 2015)
Large cystic masses originating from the retroperitoneal space are rare, and cystic tumors are often considered preferentially in the differential diagnosis. However, it is difficult to make a correct diagnosis. A 55-year-old man presented with a palpable abdominal mass. A computed tomography (CT) scan detected a mass mimicking a large cystic tumor in the retroperitoneal space anterior to the psoas muscle. The mass had an enhanced outer margin, an irregular inner margin, and several surrounding necrotic lymph nodes. However, histopathologic examination followed by an exploratory laparotomy confirmed that the mass was consistent with a tuberculous (TB) abscess. A retroperitoneal TB abscess without spinal or active pulmonary TB is very rare. To the best of our knowledge, there are no published reports of a retroperitoneal TB abscess confirmed by both CT scan and surgical pathology in the Korean literature. We report a rare case of a huge retroperitoneal TB abscess that can mimic a cystic tumor.